2007
DOI: 10.1295/polymj.pj2007025
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive Azo Polyamide Based Oligoaniline: Synthesis and Characterization

Abstract: ABSTRACT:An alternating copolymer, electroactive azo polyamide was prepared by oxidative coupling polymerization of oligoaniline macromonomer and p-phenylenediamine. The molecular structure of the polyamide was characterized by Fourier-transform infrared (FT/IR) spectra, 1 H NMR spectroscopy, elemental analysis (EA) and gel permeation chromatography (GPC). UV-vis spectrum was used to monitor the chemical oxidation process and the photoisomerization of the polymer. The electrochemical activity of the polyamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The as-synthesized polymer exhibited very good solubility in comparison to the similar polymer with azo chromophores in main chain in our previous work. 32 Its electroactive properties were similar to oligoaniline, as characterized by electrochemical method. Besides, UV-vis spectra have showed that the intrinsic photoisomerization of the azo chromophores was maintained in the polymer.…”
Section: Introductionmentioning
confidence: 91%
“…The as-synthesized polymer exhibited very good solubility in comparison to the similar polymer with azo chromophores in main chain in our previous work. 32 Its electroactive properties were similar to oligoaniline, as characterized by electrochemical method. Besides, UV-vis spectra have showed that the intrinsic photoisomerization of the azo chromophores was maintained in the polymer.…”
Section: Introductionmentioning
confidence: 91%